Are dental researchers asking patient-important questions? A scoping review. (June 2016) - Fleming, Padhraig S.; Koletsi, Despina; O'Brien, Kevin; Tsichlaki, Aliki; Pandis, Nikolaos
Abstract: Objectives: There is an increasing recognition that research outcomes should resonate with patients rather than fixating on technical aspects of interventions. We aimed to assess the nature of outcomes within a representative subset of clinical trials published in leading dental journals. Methods: Randomized controlled trials published over a 3-year period up to December 31st, 2015 were identified in eight leading general and specialty dental journals: Journal of Dental Research, Journal of Dentistry, American Journal of Orthodontics and Dentofacial Orthopedics, Pediatric Dentistry, International Journal of Prosthodontics, Journal of Endodontics, International Journal of Oral and Maxillofacial Surgery and Journal of Clinical Periodontology. The number and nature of outcomes considered within these trials were assessed. Results: Overall 220 RCTs involving 409 outcomes (257 primary and 152 secondary) were identified. Measures of disease activity were most commonly assessed as both primary (n = 91, 35%) and secondary outcomes (n = 59, 39%). Quality of life and functional measures were rarely considered as primary outcome domains. Overall, 182 (44%) outcomes were primarily clinician-focused, 140 (34%) were patient-centered, while 22% (n = 87) were both patient- and clinician- focused. Conclusions: There is an undue emphasis on technical, clinician-centered outcomes within dental research common to all specialty areas. Development and adoption of core outcome sets representing the minimum set of data that should be obtained within a dental clinical trial would assist in addressing this issue. Clinical significance: There is an acceptance that research outcomes should ultimately be of relevance and benefit to patients rather than focusing on technical aspects of interventions. This study points to an undue emphasis on technical, clinician-centered outcomes within dental research common to all specialty areas. Development and adoption of agreed dental core outcome sets would help to remedy this.